Inhibition of Neuronal Apoptosis and Axonal Regression Ameliorates Sympathetic Atrophy and Hemodynamic Alterations in Portal Hypertensive Rats - Ezkurdia, Nahia (Public Library of Science, 2014)
BACKGROUND AND AIM: A neuronal pathway participates in the development of portal hypertension: blockade of afferent sensory nerves in portal vein ligated (PVL) rats simultaneously prevents brain cardiovascular regularory nuclei activation, neuromodulator overexpression in superior mesenteric ganglia, sympathetic atrophy of mesenteric innervation and hemodynamic alterations. Here we investigated in PVL rats alterations in neuromodulators and signaling pathways leading to axonal regression or apoptosis in the superior mesenteric ganglia and tested the effects of the stimulation of neuronal proliferation/survival by using a tyrosine kinase receptor A agonist, gambogic amide. RESULTS: The neuronal pathway was confirmed by an increased neuronal afferent activity at the vagal nodose ganglia and the presence of semaphorin3A in sympathetic pre-ganglionic neurons at the intermediolateral nucleus of the spinal cord of PVL rats. Expression of the active form of tyrosine kinase receptor A (phosphorylated), leading to proliferation and survival signaling, showed a significant reduction in PVL comparing to sham rats. In contrast, the apoptotic and axonal retraction pathways were stimulated in PVL, demonstrated by a significant overexpression of semaphorin 3A and its receptor neuropilin1, together with increases of cleaved caspase7, inactive poly(ADP-ribose) polymerase and Rho kinase expression. Finally, the administration of gambogic amide in PVL rats showed an amelioration of hemodynamic alterations and sympathetic atrophy, through the activation of survival pathways together with the inhibition of apoptotic cascades and Rho kinase mediated axonal regression. CONCLUSION: The adrenergic alteration and sympathetic atrophy in mesenteric vessels during portal hypertension is caused by alterations on neuromodulation leading to post-ganglionic sympathetic regression and apoptosis and contributing to splanchnic vasodilation.